Applications and future directions for optical coherence tomography in dermatology. (8th November 2020) - Wan, B.; Ganier, C.; Du‐Harpur, X.; Harun, N.; Watt, F.M.; Patalay, R.; Lynch, M.D.
Summary: Optical coherence tomography (OCT) is a noninvasive optical imaging method that can generate high‐resolution en face and cross‐sectional images of the skin in vivo to a maximum depth of 2 mm. While OCT holds considerable potential for noninvasive diagnosis and disease monitoring, it is poorly understood by many dermatologists. Here we aim to equip the practising dermatologist with an understanding of the principles of skin OCT and the potential clinical indications. We begin with an introduction to the technology and discuss the different modalities of OCT including angiographic (dynamic) OCT, which can image cutaneous blood vessels at high resolution. Next we review clinical applications. OCT has been most extensively investigated in the diagnosis of keratinocyte carcinomas, particularly basal cell carcinoma. To date, OCT has not proven sufficiently accurate for the robust diagnosis of malignant melanoma; however, the evaluation of abnormal vasculature with angiographic OCT is an area of active investigation. OCT, and in particular angiographic OCT, also shows promise in monitoring the response to therapy of inflammatory dermatoses, such as psoriasis and connective tissues disease. We additionally discuss a potential role for artificial intelligence in improving the accuracy of interpretation of OCT imaging data.